Effects of integrated blood purification on haemodynamics and oxygen metabolism in children with severe sepsis - Hekai Ma; Zhiyuan Wang; Jiahao Geng; Junlin Zhao; Tuanjie Wang; Ling Liu; Yuping Xu; Weiqing Liu; Min Wang; Lan Zhao; Shujun Li (Frontiers in Medicine, 2024)
ObjectiveTo investigate the effects of integrated blood purification on haemodynamics and oxygen metabolism in children with severe sepsis.MethodsClinical data of 12 children with severe sepsis admitted to the pediatric intensive care unit of our hospital between October 2021 and June 2022 were retrospectively analyzed. All patients were treated with integrated blood purification, and changes in haemodynamic parameters, including heart rate, blood pressure, mean arterial pressure and cardiac output, and oxygen metabolism parameters (blood lactic acid, oxygen delivery, oxygen consumption and oxygen extraction rate) were observed before and after treatment.ResultsThe heart rate (134[106,160] vs 111[101,128], p = 0.037), central venous pressure (9[7,10] vs 8[7,9], p = 0.04), stroke output (28[18,43] vs 21[15,31], p = 0.01), blood lactate (3.3[2,4] vs 2.5[1.3,3.6], p = 0.015), oxygen consumption (165.99[121.44,230.31] vs 124.18[82.51,162.86], p = 0.041) and oxygen extraction rate (38.83[31.87,44.62] vs 28.67[21.05,32.72], p = 0.019) were decreased, whereas systolic blood pressure (97[83,104] vs 107[94,116], p = 0.033) and central venous oxygen pressure (32[29, 37] vs 39[34,46], p = 0.005) were increased in the children after treatment compared with before treatment. There were no statistically significant differences in diastolic blood pressure, mean arterial pressure, cardiac output, arterial oxygen pressure and oxygen delivery before and after treatment (all p > 0.05).ConclusionIntegrated blood purification can improve haemodynamic and oxygen metabolism parameters in children with severe sepsis, with a high value in clinical application.